Grain boundary diffusion in nanocrystalline Nd-Fe-B permanent magnets with low-melting eutectics. (15th August 2016) - Sawatzki, Simon; Kübel, Christian; Ener, Semih; Gutfleisch, Oliver
Abstract: In order to combine the good thermal stability of nanocrystalline Nd-Fe-B magnets with the efficient grain boundary diffusion process (GBDP), low-melting eutectics have been mixed with Nd-Fe-B melt-spun ribbons, hot-compacted and subsequently die-upset. Transmission electron microscopy (TEM) analysis revealed the formation of 5–10 nm thick Dy-shells and a crystallography dependent diffusion into the individual solid grains on the nanoscale. Subsequent annealing at 600 °C leads to an enhanced diffusion but also some undesired Nd-O phases and induced grain growth depending on the annealing time, degree of deformation, strain rate and position within the sample. An optimized distribution of the low-melting eutectic was realized by milling the precursor powder and by using ternary alloys with reduced melting points. As a consequence a much higher effective increase in coercivity per wt%Dy was obtained compared to a homogeneous Dy-distribution which demonstrates the validity of this new approach. Graphical abstract: Highlights: Formation of Dy-rich nano shells was observed with HR-TEM. Dy-diffusion into the individual solid grain depends on crystallograph-ic orientation. Powder milling and the usage of ternary alloys increase homogeneity and effective increase in coercivity. Faster die-upsetting suppresses grain growth and undesired phase formation and increases absolute coercive values.